Seasonal influenza vaccination: Attitudes and practices of healthcare providers in Jordan. - Olla Hamdan; Justin Z Amarin; Molly Potter; Zaid Haddadin; Ahmad Yanis; Yanal Shawareb; Najwa Khuri-Bulos; Randa Haddadin; Natasha B Halasa; Andrew J Spieker (PLoS ONE)
Background Influenza is associated with significant global morbidity and mortality, with vaccination being the primary preventive strategy. Despite recommendations, influenza vaccine uptake among healthcare providers (HCPs) remains suboptimal, especially in the Eastern Mediterranean. We aimed to assess the attitudes and practices of HCPs in Jordan regarding seasonal influenza vaccination and assess sources of variation thereof. Methods We conducted a cross-sectional survey study among a sample of HCPs practicing in Jordan (12/29/2020-04/26/2021). Participants completed a questionnaire assessing demographics, influenza vaccination history, attitudes, and practices. We used logistic regression to evaluate factors related to vaccine receipt and reasons for non-vaccination. We used proportional odds models to evaluate factors related to HCP recommendations and to compare opinions on influenza vaccination between ever- and never-vaccinated HCPs. Results Of 305 survey initiates, 206 HCPs (67.5%) comprised the analytic sample. The median age was 35 years; 61.2% were women, and 43.7% were pharmacists. Over half (52.9%) never received an influenza vaccine; however, older age and self-identifying as a physician were associated with higher odds of having ever received the influenza vaccine. The main reasons for non-vaccination were related to the misassessment of risks and benefits. Prior receipt of influenza vaccination was strongly associated with odds of recommending vaccination (or = 10.5; 95% CI = [5.38-20.3]; p<0.001). The COVID-19 pandemic reportedly enhanced influenza vaccine acceptance among 48.5% of HCPs surveyed. Conclusions Low influenza vaccine uptake among healthcare providers in Jordan is related to misassessment of risks and benefits. Enhancing attitudes and confidence through tailored education is crucial to overcoming hesitancy and promoting sustained improvements in vaccination attitudes and practices among HCPs in Jordan.